THE IMPACT OF SAFEGUARD MEАSURES IN INTERNATIONAL TRADE ON THE SOCIO-ECONOMIC DEVELOPMENT OF THE POOREST COUNTRIES - Y. K. Zaytsev (Vestnik MGIMO-Universiteta)
The article discusses the role of international trade in promoting economic growth and socio-economic development of the poorest countries. The analysis of foreign trade statistics shows that the modality of the relationship between trade and economic development has changed, depending on a large number of factors, including tariff and non-tariff such measures. In the first part of the article the author examines the theoretical concepts that describe the impact of international trade on the socio-economic development of the poorest countries. Having analyzed a wide range of literature, the author identifies two approaches to the understanding the issue, "old" one establishing a direct link between trade, economic growth and long-term development, and the "new" one problematizing this link. The second part of the paper examines the place of protective measures for trade in developing countries. It shows that the removal of the protective measures as a result of trade liberalization does not always go for the benefit of developing countries. The last part of the article evaluates the impact of protective measures on trade and economic development in the poorest countries on the basis of total trade restrictions index. The author comes to the conclusion that international trade and the strengthening of export potential should be a tool, but not the key objective of national economic policy of the poorest countries.